Types of Injuries and the Severity of Shoulder Dysfunction Associated with Diabetes Mellitus in Patients with Functional Impairment: A Case–Control Study - Mercedes Fuentes-Murguia; Karla B. Carrazco-Peña; Osiris G. Delgado-Enciso; Joel Castellanos-Gomez; Gustavo A. Hernandez-Fuentes; Fabian Rojas-Larios; Carmen A. Sanchez-Ramirez; Margarita L. Martinez-Fierro; Iram P. Rodriguez-Sanchez; José Guzmán-Esquivel; Idalia Garza-Veloz; José E. Del-Río-Valdivia; et al. (Biomedicines)
Background/Objectives: Patients with diabetes have been reported to experience a higher prevalence of shoulder disorders compared to those without diabetes or with other medical conditions. However, the specific types of shoulder injuries and the extent of functional impairment associated with diabetes mellitus remain unclear. This study aimed to assess the association between diabetes and specific shoulder injuries, as well as the degree of functional impairment in affected patients. Methods: A case–control study was conducted involving 136 patients with shoulder functional impairment (UCLA Shoulder Scale ≤ 27). The study included 38 patients with diabetes and 98 non-diabetic controls. Shoulder injuries were diagnosed using ultrasonography, focusing on the supraspinatus tendon, long head of the biceps tendon, subscapularis tendon, and the presence of adhesive capsulitis or rotator cuff tears. Results: Diabetic patients had significantly higher rates of poor shoulder function compared to non-diabetic controls (89.47% vs. 63.26%, adjusted OR [adOR] 5.22, 95% CI 1.57–17.32, p = 0.007). While both groups had high rates of supraspinatus and long head of the biceps tendon injuries (~80%), no significant differences were found between them (p > 0.300). However, diabetic patients were more than three times as likely to have subscapularis tendon injuries (adOR 3.15, 95% CI 1.26–7.90, p = 0.014) and massive rotator cuff tears (adOR 3.76, 95% CI 1.16–12.15, p = 0.027). Additionally, diabetes was associated with a fourfold increased risk of adhesive capsulitis (adOR 4.16, 95% CI 1.20–14.47, p = 0.025). Conclusions: Diabetes mellitus is linked to greater functional and structural deterioration of the shoulder, highlighting the importance of considering diabetes as a risk factor for specific shoulder injuries. Early diagnosis and treatment may improve outcomes for diabetic patients with shoulder disorders.